PENGGUNAAN KEKUATAN DALAM MENGENDALIKAN BISNIS WARALABA RITEL - Alimuddin Rizal R; Endah Mudjiasih (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2010)
Retail Business Management with a franchise system as a primary method of entering themarket has been chosen. Control of retail network of franchise become a very important. Thepurpose of this paper is to examine the Social Exchange Theory-Agency Theory and PowerTheory, implemented in cooperation relationships between the manager of a franchise business.This study examines the empirical findings from various studies about the franchise, especially onhow an organization controls the other organizations to follow what has been required under atreaty. The results of this study found that there are different patterns of business controlsimplemented by the managers of the franchise, namely: through the Contract franchise, supportmechanisms, the selection of franchise partners, the pattern of the franchise relationship and theuse of parent-area franchise system. This pattern was found as the main method used by theowners of retail businesses to control the franchise business network. Meanwhile, a source ofCoercive Power and Non-Coercive Power appears in the form of franchise contracts andfranchise relations of the dominant mechanism used by franchise businesses. However, it isrecommended to develop a pattern of relationships that use pattern-based inter-organizationalrelationships on the Relationship Power and Organizational Power.Keywords: franchise, power, control, coercive power, outcome